Regular orthoscalar representations of extended dynkin graphs E_6 and E_7 and *-algebras associatedwith them - Livins'kyi, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain a classification of indecomposable orthoscalar representations of the extended Dynkin graphs E_6 and E_7 with a special character and of the *-algebras associated with them, up to the unitary equivalence.